Medical Student Leadership Development through a Business School Partnership Model: A Case Study and Implementation Strategy. (April 2021) - Daaleman, Timothy P; Storrie, Mindy; Beck Dallaghan, Gary; Smithson, Sarah; Gilliland, Kurt O; Byerley, Julie S
Background: There is an ongoing call for leadership development in academic health care and medical students desire more training in this area. Although many schools offer combined MD/MBA programs or leadership training in targeted areas, these programs do not often align with medical school leadership competencies and are limited in reaching a large number of students. Methods: The Leadership Initiative (LI) was a program created by a partnership between a School of Medicine (SOM) and Business School with a learning model that emphasized the progression from principles to practice, and the competencies of self-awareness, communication, and collaboration/teamwork. Through offerings across a medical school curriculum, the LI introduced leadership principles and provided an opportunity to apply them in an interactive activity or simulation. We utilized the existing SOM evaluation platform to collect data on program outcomes that included satisfaction, fidelity to the learning model, and impact. Results: From 2017 to 2020, over 70% of first-year medical students participated in LI course offerings while a smaller percentage of fourth-year students engaged in the curriculum. Most students had no prior awareness of LI course material and were equivocal about their ability to apply lessons learned to their medical school experience. Students reported that the LI offerings provided opportunities to practice the skills and competencies of self-awareness, communication, and collaboration/teamwork. Discussion: Adding new activities to an already crowded medical curriculum was the greatest logistical challenge. The LI was successful in introducing leadership principles but faced obstacles in having participants apply and practice these principles. Most students reported that the LI offerings were aligned with the foundational competencies.